2015
DOI: 10.1016/j.jpeds.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing, Sleep Duration, and Childhood Overweight: A Longitudinal Cohort Study

Abstract: Objectives To examine independent associations between sleep-disordered breathing (SDB), sleep duration from birth through 6.75 years, and body mass index (BMI) through 15 years of age in a population-based cohort. Study design The Avon Longitudinal Study of Parents and Children (ALSPAC) collected parent questionnaire data on child sleep duration and sleep disordered breathing (SDB) symptoms from birth through 6.75 years and child BMI from ALSPAC research clinics (n=1,899). For SDB, logistic regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 60 publications
2
44
0
Order By: Relevance
“…Those findings underscore the potential importance of early identification and remediation of any sleep disturbance, as minimal as it may seem, as a potentially viable strategic approach for reducing childhood obesity. [63]. In summary, identification of children at risk during infancy and early childhood by periodic assessments of sleep duration, regularity or onset of sleep disorders, along with prospective interventions aiming to prolong and regularize sleep in such children should provide us with more definitive answers as to the role of sleep in the context of BMI regulation and metabolic homeostasis during the formative childhood years.…”
Section: Obesity and Sleepmentioning
confidence: 99%
“…Those findings underscore the potential importance of early identification and remediation of any sleep disturbance, as minimal as it may seem, as a potentially viable strategic approach for reducing childhood obesity. [63]. In summary, identification of children at risk during infancy and early childhood by periodic assessments of sleep duration, regularity or onset of sleep disorders, along with prospective interventions aiming to prolong and regularize sleep in such children should provide us with more definitive answers as to the role of sleep in the context of BMI regulation and metabolic homeostasis during the formative childhood years.…”
Section: Obesity and Sleepmentioning
confidence: 99%
“…In one study, children with the highest levels of sleep-disordered breathing versus those without any OSA showed higher risk of later becoming overweight [20]. In another study, OSA was related to higher diastolic and systolic blood pressure values but not changes in blood pressure after four years [49].…”
Section: Discussionmentioning
confidence: 99%
“…A few prospective studies have looked at only inflammation and overweight/obesity in association with snoring and OSA, but not in-depth the complete spectrum of cardiometabolic biomarkers [20,21]. For instance, OSA in obese children was associated with greater visceral fat area derived using MRI [22].…”
Section: Introductionmentioning
confidence: 99%
“…The confounding effect of obesity on our results should also be considered because obesity is strongly associated with SDB/OSA (27) and OSA appears to amplify the underlying systemic inflammation that is present in obesity (28). As in previous studies (27), we found that children with SDB symptoms were more likely to be overweight or obese.…”
Section: Discussionmentioning
confidence: 99%